Sale By Non-Refundable Deposit (`Arabun) and Its Contemporary Implementations - Amanullah, Muhammad (Jurnal Fiqh, 2008)
Economic activities have been tremendously increased all over the world in last few decades. Among them is a practice of receiving non-refundable deposit (?arabun) before selling vehicles, apartments, etc., renting houses, or leasing properties is well practiced both in the West and in Muslim World. The objectives of this paper are to investigate whether Islam allows the practice of receiving non-refundable deposit (?arabun) in selling, and to examine its contemporary practical implementations. In order to reach these objectives, verses of the Quran, ahadith of the prophet (p. b. u. h.) and opinions of Muslim jurists would be critically and analytically reviewed by using classical and modern works of fiqh literature. Moreover, the researcher would conduct a field study on some companies at Kuala Lumpur about their implementations of this type of sale.